Varieties developed by Dr Y S R Horticultural University, Andhra Pradesh, India (Current Horticulture, 2024)
Dr Y S R Horticultural University, has come out with development of 23 varieties of horticultural crops. All of them are capable of increasing the farmers income. The varieties are resistant/tolerant to major pest and diseases. They are high yielding, enhancing the income by increasing yield by 15-30%, as compared to the existing ones. These are also suitable for mixed cropping system, ensuring more income per unit area and additional profit to farmers. Owing to resistance/ tolerance to pests and diseases their cultivation mini mizes the pesticide residues, reduces the cost of cultiva tion and ensuring safe food production (Table 1).